Magnetised accretion discs in Kerr spacetimes : II. Hot spots - García, Federico (2016)
Context. Quasi-periodic variability has been observed in a number of X-ray binaries that harbor black hole candidates. In general relativity, black holes are uniquely described by the Kerr metric and, according to the cosmic censorship conjecture, curvature singularities always have to be clothed by an event horizon. Aims. In this paper, we study the observed light curves that arise from orbiting hotspots in thin accretion discs around Kerr black holes and naked singularities, and the effect introduced by the presence of an external magnetic field. Methods. We employ a ray-Tracing algorithm to calculate the light curves and power spectra of these hot spots as seen by a distant observer for uniform and dipolar magnetic field configurations, assuming a weak coupling between the magnetic field and the disc matter. Results. We show that the presence of an external dipolar magnetic field leads to potentially observable modifications of these light curves for both Kerr black holes and naked singularities, while an external uniform magnetic field has practically no effect. In particular, we demonstrate that the emission from a hotspot, which is orbiting near the innermost stable circular orbit of a naked singularity in a dipolar magnetic field, can be significantly harder than the emission of the same hotspot in the absence of this type of magnetic field. Conclusions. The comparison of our model with observational data may allow us to study the geometry of magnetic fields around compact objects and to test the cosmic censorship conjecture in conjunction with other observables, such as thermal continuum spectra and iron line profiles.